2018
DOI: 10.1007/s40257-018-0355-8
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer Following Solid Organ Transplantation: A Review of Risk Factors and Models of Care

Abstract: The number of solid organ transplants has been increasing annually worldwide. Advances in transplantation surgery and community awareness of organ donation have been key contributors. Combined with increased understanding of immunosuppression, there are a growing number of solid organ transplant recipients in the community as a result of improved long-term outcomes. There remains a high incidence of deaths worldwide post-transplant due to non-melanoma skin cancer (NMSC), which has greater morbidity and mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 110 publications
3
48
1
Order By: Relevance
“…The increased risk conveyed by male gender, advanced recipient age and UV‐sensitive skin phototypes is emphasized by this current study, confirming reported risk factors for primary post‐transplant skin cancer . Complementing previous studies, our results further document a decline in the impact of these established risk factors for subsequent NMSC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increased risk conveyed by male gender, advanced recipient age and UV‐sensitive skin phototypes is emphasized by this current study, confirming reported risk factors for primary post‐transplant skin cancer . Complementing previous studies, our results further document a decline in the impact of these established risk factors for subsequent NMSC.…”
Section: Discussionsupporting
confidence: 90%
“…With a typical predominance of SCC over BCC, a more than 65‐fold increased incidence of post‐transplant NMSC in OTR has been estimated compared to the general population . In addition to cumulative UV‐exposure, the most important general environmental risk factor for NMSC, important intrinsic risk factors such as sex, age and skin phototype as well as transplant‐associated factors such as type, intensity, and duration of iatrogenic immunosuppression, age at transplantation and type of the transplanted organ, have been identified by previous studies …”
Section: Introductionmentioning
confidence: 99%
“…Among potential exogenous factors, chronic exposure to substances that are both carcinogenic and responsible for the development of scleroderma (such as crystalline silica and organic solvents) may be involved. Similarly, the use of certain SSc treatments may be involved in carcinogenesis: immunosuppressants used in SSc may explain an over risk of skin cancer, already well described among transplanted patients, especially concerning bladder or hematologic cancers [9,35]. In the present study, a significant number of "late-onset" cancers were associated with immunosuppressive treatments (including azathioprine and cyclophosphamide, Supplemental Table S2b).…”
Section: Second Peak: Late-onset Cancers May Results From Multiple Intsupporting
confidence: 56%
“…At the present time, tissue engineering techniques are also being developed that allow artificially recreating remote sites of organs and tissues. In this regard, reinnervation of the muscular and skin grafts is important for the replacement of defects after extensive resection operations in oncosurgery and gross posttraumatic tissue defects [29]. At the same time, on the way to creating innervation, the problem arises the formation of NMJ.…”
Section: Resultsmentioning
confidence: 99%